Análise multitemporal do processo de desertificação na sub-bacia hidrográfica do alto Paraíba - Nascimento, Sebastiana Santos do (2015)
The United Nations (UN) defines desertification as a kind of environmental degradation that occurs in arid, semi-arid and dry sub-humid areas, this being a result of climatic variations and human activities (United Nations, 2001). In Paraíba, due to the predominantly dry climate (semi-arid and dry sub-humid), over 90% of its territory has areas susceptible to desertification (BRAZIL, 2004), and one of the areas most prone and affected by this process is the Caririmicroregion, where is inserted the hydrographic basin of the Upper Course of Paraíba River, the object of study of this work. Different intensity levels of susceptibility and occurrence of desertification can be identified from the integration of environmental and socioeconomic indicators, which can be assembled in an index to a better understanding of the process. Thus, the objective of this study was to analyze the evolutionary trend in time and space and how it is reflected in the process of desertification in the study area, from applying the methodology developed by Sampaio et al. (2003), which proposes the analysis of desertification processes from the establishment of propensity or susceptibility indexes and desertification indexes, based on the progression of process steps, such as the reduction in vegetation cover, environmental degradation, deterioration agriculture and the deterioration of social and economic conditions. The propensity to desertification kept a low propensity for 53.9% of the sub-basin in the first two decades analyzed (1990 and 2000). However, the severe level, not recorded in the first decade, now represents 21.6% of the sub-basin area in the 2000s, due to the reduction of moderate and high levels. In 2010, the low propensity level decreased 44.4%, and accounted for only 9.5% of the area of sub-basin, while the moderate level was increased from 17.6% in the previous decade to 42.6%. The high propensity level increased by 7.0% and severe level increased by 11.9%. In relation to the occurrence of desertification in AltoParaíba in the period between the decades of 2000 and 2010, overall, there was also a worsening of the problem analyzed. Areas considered notdesertified has increased by 26.4%, even with a reduction of 20.2% of the severe level, that had not been registered in the previous decade, now represents 68.6% of the sub-basin. In summary, what it can learn of the results obtained for the propensity to desertification, is that there has been deterioration in the general conditions existing in the study area, expressed by the indexes used, which meant that there was an increase in areas prone to severe desertification. With respect to the results obtained in relation to the desertification levels, it was observed that, in general, there was a worsening of the desertification situation in AltoParaíba‟s sub-basin, once there was a decrease of areas considered not desertified, it had an increase of high and severe desertification level areas, and in the last two decades, there was not occurred areas with low to moderate desertification levels.